Association of the remnant cholesterol to high-density lipoprotein cholesterol ratio with mortality in peritoneal dialysis patients - Zebin Wang; Sibing Huang; Na Tian; Qingdong Xu; Xiaojiang Zhan; Fenfen Peng; Xiaoyang Wang; Ning Su; Xiaoran Feng; Xingming Tang; Xianfeng Wu; Qian Zhou; et al. (Lipids in Health and Disease)
Abstract Background In individuals receiving continuous ambulatory peritoneal dialysis (CAPD), remnant cholesterol (RC) and high-density lipoprotein cholesterol (HDL-C) levels significantly influence clinical outcomes. Current clinical practice might benefit from assessing these two lipid markers in combination when evaluating cardiovascular disease (CVD) and all-cause mortality. Therefore, this research sought to examine how the RC/HDL-C ratio correlates with both CVD and all-cause mortality rates among individuals receiving CAPD treatment. Methods Between January 1, 2005 and December 31, 2016, a multi-center retrospective analysis of 2006 CAPD patients from five peritoneal dialysis hospitals in China was conducted. Participants were split into two subgroups in accordance with the baseline serum RC/HDL-C ratio restricted cubic spline cutoff value. The correlations between mortality and RC/HDL-C ratio were examined through case-specific hazard modeling. Results The observation period documented 549 all-cause fatalities, with cardiovascular deaths accounting for 269 cases. The Kaplan-Meier analysis revealed statistically significant divergence in both all-cause mortality (log rank test P < 0.001) and CVD mortality (log rank test P = 0.003). Elevated RC/HDL-C ratios showed increased hazard ratios (HR) for all-cause mortality (1.335, 95% CI, 1.112–1.603, P = 0.002) and CVD mortality (1.319, 95% CI, 1.013–1.717, P = 0.040) compared to lower ratio counterparts. Nevertheless, no statistically meaningful association was found between CVD mortality and either RC (HR: 1.296, 95% CI, 0.992–1.691, P = 0.057) or HDL-C (HR: 0.887, 95% CI, 0.680–1.157, P = 0.376). Conclusion The RC/HDL-C ratio independently predicts mortality in CAPD patients, persisting as a significant prognostic marker after multivariable adjustment.